Bodily Intimacy and its Neurobiological Foundations - Conill, Jesús (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
The first part of this study stresses the importance of intimacy for human life and defends the biological standpoint against the functionalist computational stance. This is based on the concept of bodily subjectivity in Nietzsche, bodily, emotional and spiritual intimacy in Ortega y Gasset, and bodily and personal intimacy in Zubiri. The second part sets forth a significant selection taken from studies on the neurobiological foundations of bodily intimacy, reaching beyond sterile reductionisms: its possible neuronal substrate (the neurology of intimacy?), the brain as selectional system, mirror neurons, synaesthesia and neurophenomenology. It ends by putting forward the problem of the power of intimacy, the conflict between this and the reputation.